EVALUASI KESESUAIAN LAHAN AGROFORESTRI BERBASIS TANAMAN HORTIKULTURA DI DESA KARYASARI, KECAMATAN LEUWILIANG, KABUPATEN BOGOR: Land Suitability Evaluation for Agroforestry Based on Horticultural Crops in Karyasari Village, Leuwiliang District, Bogor Regency (Jurnal ForestrIndo, 2025)
Karyasari Village exhibits low agroforestry productivity, particulary in horticultural crops. A land suitability evaluation is required as a strategy for agricultural development, integrating field data with land suitability classification for horticultural crops. This evaluation employs both matching and scoring methods, yielding four suitability classes (S1, S2, S3, and N). The study’s findings indicate that tree horticultural crops preferred by farmers are avocado, coffee, and cassava. The weighted scores for these crops range between 60-80, with low soil organic-carbon content and steep land slopes identified as limiting factors. This places all community forest land in Karyasari Village whitin the S2 category (moderately suitable).